The use of platelet-rich plasma injections in the treatment of knee osteoarthritis - review of the literature - Banatkiewicz, Joanna; Bartkowska, Oliwia; Czarnecka, Sofia; Łuczyńska, Gabriela; Deka, Emilia; Dobosz, Adam; Domińczak, Jan; Babik, Karolina; Bojanowska, Hanna; Wojnowski, Antoni (Journal of Education, Health and Sport, 2026)
Introduction: Knee osteoarthritis (KOA) is one of the most common degenerative joint diseases, affecting millions of people worldwide. It is characterized by progressive cartilage degradation, chronic pain, joint stiffness, and functional impairment. Traditional treatment methods, including pharmacotherapy and intra-articular injections of corticosteroids or hyaluronic acid, provide limited and often short-term relief. Platelet-rich plasma (PRP) has emerged as a promising regenerative therapy due to its high concentration of growth factors that may stimulate tissue healing and reduce inflammation. Objective: The aim of this study is to review the latest literature on the use of platelet-rich plasma injections in patients with knee osteoarthritis. Material and methods: A literature review was conducted on databases such as PubMed, Google Scholar, and SciSpace using the terms: "knee osteoarthritis", "platelet-rich plasma", "PRP injections", "intra-articular injections", "knee OA treatment". Conclusions: Knee osteoarthritis is a highly prevalent condition that significantly impacts quality of life. Platelet-rich plasma has demonstrated positive effects on pain reduction and functional improvement in patients with KOA. PRP injections lead to superior outcomes compared to placebo and hyaluronic acid, with therapeutic effects lasting 12-24 months. However, there is lack of standardization in PRP preparation protocols, and further studies are necessary to establish optimal treatment parameters.